2022
DOI: 10.3390/jcm12010126
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics of Primary Pulmonary Hodgkin Lymphoma (PPHL): Two Institutional Experiences with Comprehensive Literature Review of 115 PPHL Cases

Abstract: Primary pulmonary Hodgkin lymphoma (PPHL) is an extremely rare condition. Its clinicopathological characteristics remain unclear because of the limited number of patients with PPHL. The aim of this study was to comprehensively analyze the clinicopathological characteristics of PPHL. We reviewed the electronic medical records and pathology slides of our 10 PPHL patients. The female-to-male ratio was 6:4, and the mean age was 41 years. Although three patients had no symptoms, seven had localized or generalized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…Also, the most common type of HL in this study was Nodular Sclerosis, which is consistent with previous finding (Jung et al, 2022). In examining the relationship between HL type and other variables, two types of Lymphocyte-Rich and Lymphocyte-Depleted were not included due to the very small sample size.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, the most common type of HL in this study was Nodular Sclerosis, which is consistent with previous finding (Jung et al, 2022). In examining the relationship between HL type and other variables, two types of Lymphocyte-Rich and Lymphocyte-Depleted were not included due to the very small sample size.…”
Section: Discussionsupporting
confidence: 88%
“…The mean age of total patients in the study was 34.03±15.78 years, ranging from 8 years to 76 years. This age was lower than previous studies (Jalili et al, 2022;Jung et al, 2022), but another study showed a bimodal age curve (a mode at 15 ~ 35 years of age and the second mode in elderly) (Nakatsuka and Aozasa, 2006). These differences may note the various age specific relation for the HL however a in Iran (Monabati et al, 2020) and China (Jalili et al, 2022) reported a rather similar age.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, this study included patients who underwent various treatments, including radiation, surgery, or chemotherapy, with the latter primarily being the MOPP regimen (mechlorethamine, vincristine, procarbazine, prednisone), which is currently not recommended. Conversely, recent analyses and individual case reports on ABVD administration are optimistic, demonstrating mostly CR in patients [ 17 , 18 ]. Given these circumstances, the prognosis of PPHL and the outcomes of novel chemotherapy regimens remain uncertain, necessitating further studies involving a larger patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary involvement of secondary HL is not uncommon and is reported to occur in 15–40% of patients. 1 , 2 …”
mentioning
confidence: 99%